PENGENALAN ANALISIS STANDAR BELANJA SEBAGAI INSTRUMEN PENYUSUNAN ANGGARAN BERBASIS KINERJA: UPAYA PENINGKATAN KAPASITAS ANGGOTA DPRD KABUPATEN CILACAP DALAM PENYUSUNAN APBD - Alizar Isna (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
One of the duties of DPRD members is to prepare and stipulate Regional Regulations (Perda) on the Regional Revenue and Expenditure Budget (APBD). In accordance with the laws and regulations that govern it, the preparation of the APBD is based on performance so that the preparation process must use the Standard Spending Analysis (ASB) as one of its instruments. In order for DPRD members to understand the concept of ASB and its function in preparing the budget, the material